DLX3 mutation negatively regulates odontogenic differentiation of human dental pulp cells. (May 2017) - Zeng, Li; Zhao, Na; Han, Dong; Liu, Haochen; Liu, Yang; Wang, Yixiang; Feng, Hailan
Highlights: Our research group collected a novel de novo mutation of DLX3 in a Chinese TDO patient. Novel de novo mutation of DLX3 down-regulated the ALP activity and calcified capacity of hDPCs. Novel de novo mutation of DLX3 significantly inhibited the proliferation and odontogenic differentiation of hDPCs. Abstract: Objectives: The purpose of this study was to investigate the role of a novel mutant DLX3 on the odontogenic differentiation of human dental pulp cells (hDPCs) in tricho-dento-osseous (TDO) syndrome. Design: hDPCs were obtained from the healthy premolars, stably-expressing wild-type DLX3 (WT), novel mutant DLX3 (Mu) and control vector (NC) cells were generated using recombinant lentiviruses. The proliferation rates of WT-hDPCs and Mu-hDPCs were measured by CCK8 assay. Odonto-differentiation of hDPCs was assessed by alkaline phosphatase (ALP) activity assay, and mineralization ability was assessed by Alizarin red staining. Odontogenic markers, including DMP-1, DSPP, Nes, ALP, and DLX5, were analyzed using real-time polymerase chain reaction (qPCR). DMP-1 and DSPP expressions were further confirmed by Western blotting. Results: CCK8 results showed that the novel mutant DLX3 decreased the proliferation rate of hDPCs compared with wild-type DLX3. qPCR showed that the novel mutant DLX3 weakened odontogenic differentiation by downregulating the expression of odontogenic genes. These results were further confirmed by Western blotting and ALP activity assay. Additionally, Alizarin red staining showed that the novel mutant DLX3 decreased the mineralization of hDPCs compared with wild-type DLX3. Conclusions: Novel de novo mutation of DLX3 significantly decreases the proliferation rate and inhibits the odontogenic differentiation and mineralization of hDPCs, suggesting that this novel mutation of DLX3 can influence the dentinogenesis in TDO syndrome.